Analysis of Accountability, Transparency and Participation of Village Funds Management in Pejambon Village, Sumberrejo District, Bojonegoro District - Hertati, Diana; Tukiman (Nusantara Science and Technology Proceedings, 2020)
The purpose of this study is to analyze the accountability, transparency, and participation of village fund management by the village government which starts from the planning, implementation, administration, reporting, and accountability stages. This study bases literature and Minister of Home Affairs Regulation No. 113 of 2014 as an indicator in the management of village funds. This study was conducted in Pejambon Village, Sumberrejo District, Bojonegoro Regency, through primary and secondary data collection. Analyzes were performed with an interactive model from Miles and Huberman (2014). The results showed the accountability of village fund management had been applied following the specified principles. At every stage in the process of managing village funds, it has been carried out transparently by actively involving the community. Administration and reporting are done through the standard mechanism, although a bit late. While the accountability has been done through various media both online and offline.